Contextualism in Mosque Architecture: Bridging the Social and Political Divide - Rasdi, Mohammad Tajuddin Mohd (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2017)
The expression of architecture in mosques in the non-Muslim worlds may have added to the problem of alienization of Muslims to the host community. The Muslim community has misunderstood the idea of ‘sacredness’ of form in allowing revivalistic foreign traditional architectural language to be part of the mosque architectural language. This sets up the mosque being totally not in context with the surrounding urban fabric. This paper outlines the hadith of the Prophet Muhammad about the importance of being part of a larger society of man and even to love all man regardless of their faith. Hence, this paper puts forward the position that mosque designers must rethink their design ideas towards the values of inclusivity in Islam.